Investigating the Linkages Between Migration and Image of the City - Samruddhi Sachin Purohit; Vaishnavi Shevde; Shruti Joshi; Amruta Garud; Surbhi Gadkari; Mandar Athavale (Alanya Üniversitesi, 2024)
This study explores the complex interplay between migration and the image of the city, with a focus on the Hadapsar-Magarpatta area of Pune, India. Using Kevin Lynch's theoretical framework of urban elements—districts, paths, nodes, landmarks, and edges—combined with Geographic Information System (GIS) analysis, the research investigates how migration reshapes urban form and identity. The study employs a decadal analysis of urban transformation, identifying key changes driven by migration patterns. Findings reveal that migration significantly influences the development of new urban nodes, alters paths, and affects the overall spatial structure, leading to evolving city identities. The influx of migrants is found to enhance the functional complexity of urban districts, impact the hierarchy of nodes, and reconfigure the prominence of paths within the city's spatial organization. This transformation contributes to socio-economic shifts, influencing local economies, labor markets, and resource distribution patterns. The study underscores the importance of integrating migration dynamics into sustainable urban planning, promoting the need for resilient infrastructure and inclusive policies to accommodate demographic changes. This research contributes to urban morphology literature by providing new insights into how migration drives urban transformation, reshaping the image and functionality of cities in a rapidly urbanizing world.